2016
DOI: 10.5665/sleep.5624
|View full text |Cite
|
Sign up to set email alerts
|

Association between Snoring and Leukocyte Telomere Length

Abstract: Our findings suggest that snoring may influence telomere attrition independent of sleep apnea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
0
3
1
2
Order By: Relevance
“…Previous reports suggest that women have at least a 40% increased risk of insomnia compared with men (Guidozzi, 2015). Gender differences in associations between sleep and LTL have not been investigated in any populations although associations between sleep duration, snoring or circadian rhythm disturbance, and LTL were reported (Barceló et al, 2010;Carroll et al, 2016;Shin et al, 2016;Wynchank et al, 2019). Our study showed that sleep quality was associated with LTL in female patients but not in male patients.…”
Section: Discussioncontrasting
confidence: 56%
“…Previous reports suggest that women have at least a 40% increased risk of insomnia compared with men (Guidozzi, 2015). Gender differences in associations between sleep and LTL have not been investigated in any populations although associations between sleep duration, snoring or circadian rhythm disturbance, and LTL were reported (Barceló et al, 2010;Carroll et al, 2016;Shin et al, 2016;Wynchank et al, 2019). Our study showed that sleep quality was associated with LTL in female patients but not in male patients.…”
Section: Discussioncontrasting
confidence: 56%
“…Consistent with this finding, we observed shorter TL among adolescents with the dual burden of atopic disease and snoring than those with either snoring or atopic disease. A possible explanation for this finding is the elevation of inflammation and oxidative stress caused by the stacking burden of atopic disease and snoring [ 11 , 21 ]. For example, the mechanical stress that arises from repetitive vibrations and airway pressure gradients during snoring may stimulate systemic inflammatory responses [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of snoring may also affect cellular functions. For example, a recent study found shorter telomeres in patients with snoring when compared to healthy individuals [ 21 ]. However, little has been done to clarify the effect of co-occurrence of snoring and atopic symptoms on cellular functions, particularly, in young populations.…”
Section: Introductionmentioning
confidence: 99%
“…Динамічна МРТ-візуалізація, ендоскопія уві сні і записи імпедансної манометрії глотки встановили той факт, що як хропіння, так і обструктивне апное сну (ОАС) є багаторівневими явищами, при яких турбулентний потік повітря може бути пов'язаний з обструкцією в носовій порожнині, ротовій порожнині і області гіпофарінксу [3][4][5][6][7]. Це явище спостерігається в різних пропорціях у різних пацієнтів.…”
Section: оглядиunclassified
“…Отже, як хропіння, так і обструктивне апное сну є мультіетіологічною проблемою, для усунення якої потрібно чітке усвідомлення того моменту, що обструкція може бути на декількох рівнях одночасно і далеко не у всіх випадках причиною хропіння є збільшення uvula та зниження тонусу м'якого піднебіння [4][5][6].…”
Section: оглядиunclassified